The Perceived Waiting Time versus the Actual Drug Waiting Time in the Outpatient Pharmacy at Persada Hospital - Setiawati, Lisa (Brawijaya University, 2018)
The target of quality service for Persada Hospital outpatient pharmacy has been achieved in which the average time spent on waiting for the non-compounded drug is 11 minutes and for the compounded drug is 25 minutes. That achievement has not been able to alter the perceived length of the drug waiting time at the outpatient pharmacy evidenced by the number of losses resulting from unattended prescriptions due to the long wait. This study is aimed to find out and analyze the main factors leading to the perceived length of drug waiting time at the outpatient pharmacy and come up with alternative solutions thereto. The employed method in this study is descriptive qualitative research comprising the observation, interview and the collection of secondary data. The researchers conducted an observation on the process and flow of the prescription service of the outpatient pharmacy and proceeded to the focus group discussion to discover the main problems using Fish Bone Diagram. Â The uncertain length of the wait time was found to be the major cause. To resolve the issue of the uncertainty of the waiting time, the Time Motion Study was conducted on the service response time as a follow up by providing the estimated waiting duration guide (information) Â for the outpatient pharmacy. This guide comprises 3 categories of the service waiting time of 10-15 minutes, 25-45 minutes, and 25-60 minutes.Â